Future prospective of bioethanol production from sugar palm sap - Mustofa; Hariadi (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2024)
The availability of fossil fuels is decreasing along with increasing environmental temperatures due to their use. Therefore, there is a need for other alternatives to overcome this problem, such as the use of bioethanol as an environmentally friendly renewable energy. This research was aimed to identify the potency of sugar palm (Arenga pinnata Merr) sap as a feedstock for bioethanol production. Two major aspects of the identification focus were the feedstock availability and the bioethanol production process. The feedstock identification was conducted by surveying the industry of sugar palm and collecting data of the volume of sugar palm sap. Then, the production process of bioethanol as final product was conducted in four stages. They are characterization of samples, pasteurization, fermentation, and distillation. The results show that sap samples collected from the farmers have pH = 3.1-3.2, density 0.96 gr/mL, and carbohydrate content 1.51%, respectively. Sugar palm sap was fermented with 0.03 m/v fermentation agent of yeast within 72 hours. After the fermentation process, the sugar palm sap contains 1.51% carbohydrates, 74% alcohol, and 63.96% ethanol. Furthermore, the distillation temperature of 78-80oC resulted in a 7.44% v/v ratio of extract amount from the total volume of the distillation results. The bioethanol quantity can be increased by considering the process, especially during the fermentation.